South Africa and Sweden: A Story of Solidarity, Trust, and Shared Common Values - Håkan Juholt (The Thinker)
I have a beautiful painting of Oliver Tambo and Olof Palme in my off ice. Every day, I look into the eyes of these humanitarian role models. I see a pair of committed leaders sharing hopes, commitments, and respect for one another and other human beings. I see their eyes telling me the story of a unique relationship between South Africa and Sweden, one of trust and shared common values. How did two nations, separated by more than just geography, build such a strong bond in the beginning of the 1960s? Sweden was at that stage an industrialised, prosperous, and stable country with many years of economic growth and progress, while South Africa was a repressive apartheid state where the people suffered. A unique aspect of the relationship was that it was driven by the unique people of each of these nations, with a realisation that their common goals could not be reached in isolation but through an interconnectedness that moved mountains and split oceans apart, joining our two nations for endless opportunities, for years to come.